THE INCOME STATEMENT AND ITS SIGNIFICANCE IN FINANCIAL REPORTING. - Tilly, Virgil S. (The Accounting Review, 1948)
The article presents information on income statement and it's significance in financial reporting. The development of the corporate form of organization continues to emphasize the primary importance of the income statement in financial reporting. A few years ago the balance sheet was considered to be of primary importance. Even now some think that the submission of a balance sheet is adequate. Those versed in accounting know that both the balance sheet and the income statement are needed in order reasonably to appraise the financial condition of an enterprise at a given moment. Since 1939 thirty-three Accounting Research Bulletins have been issued by the Committee on Accounting Procedure of the American Institute of Accountants and, indicative of the recognition of the importance of the income statement in financial reporting, with a few exceptions they treat primarily of the income statement. The objective has been to narrow the area of difference in practice and to establish a basis of greater uniformity with respect not only to the composition of items included in the income statement, but also as to their presentation. In attaining these objectives, people must recognize that the income statement should be informative and it should reflect the facts in accordance with accepted accounting practice.